Pengaruh Hambatan Samping Terhadap Kinerja Jalan (Studi Kasus : Mall Panakkukang Jl. Boulevard, Kota Makassar) - Agata Makupiola, Christy (Civil Infrastructure Engineering and Architectural Design, 2025)
One of the disturbances to road performance that can cause traffic flow conflicts is the entry and exit of vehicles on the roadway, vehicles stopping and parking, as well as vehicles decelerating. The main objective of this study is to determine the extent to which side friction affects the performance of the Boulevard lane. Observations were conducted on Saturday, Sunday, and Monday. Data collection was carried out through direct field observation to obtain data on side friction, traffic flow, and the average vehicle speed, with a 15-minute interval. The data were then analyzed using the PKJI 2014 method. After going through several stages of data analysis, it can be concluded that traffic flow has the highest correlation value (R²), with vehicle entry and exit on the roadway showing a value of 0.5122. Meanwhile, the relationship between side friction and the degree of saturation has a correlation (R²) of 0.947. The results of the analysis indicate that 94.7% of the changes in side friction significantly affect the degree of saturation.